A Critical Study of Gender Mainstreaming in Regional Development through Gender Responsive Planning and Budgeting Policy (PPRG) - Arifah, Kuni Nasihatun; Rahmad, Noor (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Gender mainstreaming in Indonesia is still experiencing problems even though there arejuridical rules that regulate it, regional autonomy policies that are considered capable ofanswering the problem of gender equality have not been able to answer them eventhough they have been mandated in various laws and regulations. This research willexamine gender mainstreaming in regional development through gender responsivebudgeting planning policies. The research method uses normative legal research methodswith secondary data sources in the form of legal materials. The results of the study showthat the juridical basis for implementing gender mainstreaming policies in the regionsthrough PPRG already exists in both international and national legal instruments.Furthermore, the problem of PPRG policy is the inability to understand the concept ofgender mainstreaming by regional development actors, besides that genderdisaggregated data is not available and is still a problem in gender mainstreaming bothat national and regional levels. In addition, the existing budget is only interpreted as abudget based on gender justice alone but has not fully addressed the problems of gendermainstreaming. Under these conditions, legal reconstruction, supervision and monitoringmechanisms are needed.